Fuller, Norma, Difficult to be a man: new latinamerican masculinities. Lima: Fondo Editorial de la Pontificia Universidad Católica del Perú, 2018, 198 pp. ISBN 978-612-317-406-4. - Castillo Guzmán, Gerardo (2020)
Based on case studies in Mexico, Chile and Peru, researchers from anthropology, sociology, education and psychology, provide novel material and analytical approaches to understand the complex redefinitions, resistances and permanence that men in urban societies in Latin American  experiment in their masculine identities.